Family support for physical activity post‐myocardial infarction: A qualitative study exploring the perceptions of cardiac rehabilitation practitioners. (26th January 2021) - Birtwistle, Sarah B.; Jones, Ian; Murphy, Rebecca; Gee, Ivan; Watson, Paula M.
Abstract: Physical activity post‐myocardial infarction has numerous health benefits, yet uptake through cardiac rehabilitation is poor. Whilst family support can facilitate patients' recovery, little is known about the role family may play in supporting physical activity for post‐myocardial infarction patients. This qualitative study used semistructured interviews with 14 cardiac rehabilitation practitioners to explore their perceptions about the role of the family in supporting post‐myocardial infarction patients' physical activity. Data were transcribed verbatim and analyzed thematically. Three familial roles were identified: "family as a second pair of ears, " "family as physical activity regulators, " and "family as social support." A fourth theme, "factors that influence family support, " described how family health beliefs and perceptions could influence the physical activity support provided. Practitioner perceptions suggest families play an important role in post‐myocardial infarction patients' physical activity, which is enhanced when families personally value physical activity. Integrating the family into cardiac rehabilitation may help facilitate physical activity‐related interactions and promote positive engagement for patients.